The effect of emotional and attentional load on attentional startle modulation - Adam, A.; Mallan, K.; Lipp, Ottmar (Elsevier BV, 2009)
The interactive effects of emotion and attention on attentional startle modulation were investigated in two experiments. Participants performed a discrimination and counting task with two visual stimuli during which acoustic eyeblink startle-eliciting probes were presented at long lead intervals. In Experiment 1, this task was combined with aversive Pavlovian conditioning. In Group Attend CS+, the attended stimulus was followed by an aversive unconditional stimulus (US) and the ignored stimulus was presented alone whereas the ignored stimulus was paired with the US in Group Attend CS-. In Experiment 2, a non-aversive reaction time task US replaced the aversive US. Regardless of the conditioning manipulation and consistent with a modality non-specific account of attentional startle modulation, startle magnitude was larger during attended than ignored stimuli in both experiments. Blink latency shortening was differentially affected by the conditioning manipulations suggesting additive effects of conditioning and discrimination and counting task on blink startle. © 2009 Elsevier B.V. All rights reserved.